The mediating role of cognitive emotion regulation strategies in the development of social behavior among adolescents - Roslan, Samsilah; Zakaria, Norhayati; Siaw, Yan Li; Ahmad, Noorlila (Universiti Putra Malaysia Press, 2020)
This study aimed to investigate the mediating role of cognitive emotion regulation strategies in predicting emotional intelligence, spiritual intelligence, and parent-peer attachment towards social behavior among adolescents. A quantitative approach was utilized to gather the information through survey forms. A comparative causal-effect study design was applied and five instruments were used for data collection. In addition, a structural equation modeling was conducted to test the effect of the mediator variables of cognitive emotion regulation strategies on 538 secondary school students selected from five zones identified as north, south, west, east and East Malaysia. The results showed cognitive emotion regulation strategies fully mediated the effects of emotional intelligence and closeness on social behavior. The results also reported that the cognitive emotional regulation strategies were significant as partial mediators of the relationship between the spiritual intelligence and social behavior. As a result, this study proposes a mediation model to support the combination of psychological theories from the emotional, spiritual and cognitive regulation aspects. In summary, the findings of this study recognized the factors that contribute to the social behavior among adolescents, which is crucial to policy makers in developing a prevention and intervention program.